Hydrogen and oxygen stable isotope variations of daily precipitation from 2014-2018 in the central United States - Chao Tian; Lixin Wang (PANGAEA, 2018)
Stable isotopes of hydrogen and oxygen (δ2H, δ18O and δ17O) serve as powerful tracers in hydrological investigations. To our knowledge, daily precipitation isotope record especially 17O-excess is rare in the mid-latitudes. To fill such knowledge gap, daily precipitation samples (n = 446) were collected from June 2014 to May 2018 in Indianapolis, Indiana, U.S. A Triple Water Vapor Isotope Analyzer (T-WVIA) based on Off-Axis Integrated Cavity Output Spectroscopy (OA-ICOS) technique was used to concurrently measure precipitation isotopic variations (δ2H, δ18O and δ17O). Meanwhile, 17O-excess and d-excess as second-order isotopic variables were calculated to provide additional information on precipitation formation and transport mechanisms. This study presents a four-year daily precipitation isotope dataset for mid-latitudes, and makes it available to researchers around the world who may use it as a reference for site comparisons and for global hydrological modeling validation.
Supplement to: Tian, C; Wang, L (2019): Stable isotope variations of daily precipitation from 2014–2018 in the central United States. Scientific Data, 6, 190018, https://doi.org/10.1038/sdata.2019.18